Bentuk Pertunjukan Group Gandang Tambua dan Talempong Pacik Sanggar Bukik Junjuang Sirih Nagari Paninggahan Kabupaten Solok - Aan Nursyam; Emridawati Emridawati; Hamzaini Hamzaini; Nofridayati Nofridayati; Yusnelli Yusnelli (SENDRATASIK UNP, 2022)
The purpose of this study was to determine and describe the form of performances of the Gandang Tambua and Talempong Pacik music groups at the Bukik Junjuang Sirih Nagari Paninggahan Studio. The research method applied in this research is descriptive qualitative. The result showed that the Gandang Tambua and Talempong Pacik Bukik Junjung Sirih music groups performed at various event and events such as accompanying the Datuk/Pangulu appointment procession, wedding parades (Anak Daro and Marapulai), Qur’an Khatam parades, independence day events and Minangkabau music festival. The performances of the Gandang Tambua and Talempong Pacik groups Bukik Junjung Sirih consisted of several Talempong motifs, namely Cak Dindin, Siamang Tagagau, and several motifs of the Gandang Tambua game, namely Siontong Tabang  and Hoyak Tabuik.